G148 Development of a paediatric endoscopy global rating scale: Results of a national pilot. (24th May 2017) - Narula, P; Broughton, R; Bremner, R; Piggott, A; Rawat, D; Cullen, M; Afzal, NA; Howarth, L; Gillett, P; Henderson, P; Venkatesh, K; Tzivinikos, C; et al.
Abstract : Aim: To develop a paediatric endoscopy GRS (P-GRS) as a quality improvement tool which would also define standards for accreditation of paediatric endoscopy services. Methods: A P-GRS working group was established in May 2015 and the membership of this group evolved to include representatives from the BSPGHAN endoscopy working group, district general hospital, paediatric surgery, allied health professional, and specialist input from the Joint Advisory Group in GI endoscopy. A draft P-GRS was developed following extensive discussion and communication between the P-GRS working group and the JAG and revised following a consultation period. Nine sites nationally piloted the P-GRS following a training day organised by JAG. Services are required to score a Level B in all standards. The first assessment against the P-GRS was completed in June 2016.A second assessment is to be completed in December 2016 and the results of this will be available before the meeting to present. Results: Eight of the nine pilot sites completed a GRS assessment in June 2016. In the clinical quality domain, 12% of units achieved a level B or above in the leadership and organisation standard, 25% in safety, 63% in comfort, 25% in quality, 38% in appropriateness and 50% in results. In the quality of patient experience domain, 38% of the units achieved a level B or above in the respect and dignity standard, 24% in the consent process, 38% in the patient environment and equipment, 12% in access and booking, none in productivity and planning, 38% in aftercare and none in patient involvement. In the workforce domain, 12% of the units achieved a level B or above in the teamwork standards, 26% in workforce delivery, 38% in professional development. In the training domain, none of the units achieved a level B or above. Conclusion: These results highlight a need for improvement and all pilot units agreed this was a positive experience which enabled the units to develop an action plan and share good practice. All pilot sites reflected on the measures in the P-GRS to ensure they were relevant to paediatric endoscopy services and fit for purpose.